Climatic Factors Of Architecture Used In Building Design Of Association Of Visual Arts Of Fars – Shiraz - Ghooei, Moslem Saman; Shojaei, Alireza (The Turkish Online Journal of Design Art and Communication, 2016)
The objective of the present study was to investigate the climatic factors of architecture used in building design of Association of Visual Arts of Fars – Shiraz. Methods: In the present study, descriptive – libraries and descriptive - analytic method was used. Results: By investigating the different climatic factors and geographical location of the city of Shiraz and also the investigating the impact of climatic conditions on the formation of other buildings, the climatic factors of architecture used in building design of Association of Visual Arts of Shiraz was more pronounced. In designing listed building from climatic conditions of region to improve the life and well-considered energy consumption is also improved. Another feature that has been considered in the design and construction are as follows. Considering the above and visit the city map, the site with an area of 7000 square meters in the neighborhood of Hafeziyeh with a vision to the historic fabric of the city is located. Piece of land of the historic fabric of the city of Shiraz between two Adabiyat and Haft Tan streets which is located in the North East of Shiraz, this site is located on the back of Hafeziyeh with a slope of about 5 percent. This site is to the north overlooking Haft Tan and Jahan Nama Garden and the south side is overlooking Hafeziyeh.
Keywords: City of Shiraz; Shiraz climatic conditions; Architecture of Association of Visual Arts